Characteristics of Post Socialist Spatial Development of the Functional Urban Area of Veszprém, Hungary - Iváncsics, Vera; Filepné Kovács, Krisztina (Journal of Environmental Geography, 2019)
The post-socialist era resulted remarkable changes in urban landscape in Eastern Europe and in Hungary. The special circumstances caused moderate level of urbanisation and special patterns of urban sprawl, traceable in land use changes. The urban sprawl and suburbanisation became an important trend around smaller Hungarian cities as well. Regulators are eager to rule the evolution of spaces, however, it is hard to control all aspects of land use. The research presented in this paper shows the dynamics of new artificial areas with the help of land use changes from the Corine Database for the functional urban area around Veszprém and attempts to find the most important policy responses to the growing artificial surfaces after transition. The research questions are: What are the most important trends in changing in-built areas in a small city after the transition? What kind of new artificial areas appeared and where are they situated? Were the land use plans and nature protection effective tools for manage urban sprawl? With the help of Corine land use changes between 1990-2018 the most important spatial changes are shown, and the different peri-urban areas are compared around the core town. Attention is drawn to the importance of regulation for sustainable land use and protection of resources. It also highlights the importance of the regulatory power of municipalities. Changes in the environment of Veszprém may give inspiration for the rethinking the relationship of urban-rural, and catchment area and core town.